INTERNET SEBAGAI SALAH SATU SUMBER BELAJAR PADA MATA KULIAH INTRODUCTION TO LINGUISTICS - Saleh, Suhaini M.; Sudartinah, Titik (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
This article aims at describing the roles of the internet as a learning resource for students of Introduction to Linguistics at the Study Program of English Language and Literature, Yogyakarta State University. The research was a classroom action research conducted in a class consisting of twenty students in their third semester. In the research, the students were guided in order that they can maximize the use of the internet as an additional learning resource in the subject. The results of the research show that the internet is a useful medium from which students gain a lot of advantages that make them have higher motivation to learn linguistics. Thus, the students achieve higher marks at the end of the course.